Bayesian methods in health economics: prior distributions 2 - O'Hagan, Anthony (Henry Stewart Talks, 2009)
Prior information, Prior probability distribution, Weak prior distribution, Informative prior distributions, Elicitation, Heuristics and biases, Case study in drug development, Simulating SVEs, Multivariate elicitation, Hierarchical models
Reviewed at 2022/03/30